Early Arsakid Parthia (ca. 250-165 B.C.) : At the Crossroads of Iranian, Hellenistic, and Central Asian History - Olbrycht, Marek Jan (Mnemosyne Supplements Online, Supplement 2020, ISBN: 9789004419193., 2021)
In his new monograph Early Arsakid Parthia (ca. 250-165 B.C.): At the Crossroads of Iranian, Hellenistic, and Central Asian History , Marek Jan Olbrycht explores the early history of the Arsakid Parthian state. Making use of literary and epigraphic evidence as well numismatic and archaeological sources, Olbrycht convincingly depicts how the Arsakid dynasty created a kingdom (248 B.C.-A.D. 226), small at first, which, within a century after its founding, came to dominate the Iranian Plateau and portions of Central Asia as well as Mesopotamia. The "Parthian genius" lay in the Arsakids' ability to have blended their steppe legacy with that of sedentary Iranians, and to have absorbed post-Achaemenid Iranian and Seleukid socio-economic, political, and cultural traditions.